2010
DOI: 10.1002/jrs.2646
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic discrimination of pigments and tempera paint model samples by principal component analysis on first‐derivative spectra

Abstract: This work explores the application of principal component analysis (PCA) on first-derivative Raman spectra to investigate historical tempera paint model samples. Various paint model samples were prepared containing pure blue pigments (azurite, lapis lazuli and smalt), pure red pigments (cinnabar, minium and raw Sienna), pure white pigments (lead white, chalk and gypsum), pure egg yolk as binder and tempera model samples obtained by mixing each of the pigments with the binder, and further characterized by Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 39 publications
2
49
0
Order By: Relevance
“…In this sense, previous research has demonstrated the benefit of applying spectral data coupled with a multivariant analysis (e.g., Principal Component Analysis, PCA) to detect structural interactions and alteration processes in painting materials . However, very little research has been done on the combined use of these techniques in ancient glass and enamels.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, previous research has demonstrated the benefit of applying spectral data coupled with a multivariant analysis (e.g., Principal Component Analysis, PCA) to detect structural interactions and alteration processes in painting materials . However, very little research has been done on the combined use of these techniques in ancient glass and enamels.…”
Section: Introductionmentioning
confidence: 99%
“…The work presented by Navas et al [17] explores the application of principal component analysis (PCA) on firstderivative Raman spectra to investigate historical tempera paint model samples. Nineteen model samples were prepared according to Old Master recipes to obtain egg yolk tempera painting standards (several pigments covering blue, red and white colours) similar to those used by medieval artists.…”
Section: New Methods and Techniques For Complex Mixturesmentioning
confidence: 99%
“…Recent authors have proposed the use of spectroscopic techniques, as vibrational and electronic spectroscopic methods, coupled with multivariate analysis for the discrimination of different painting binders (animal glue, whole egg, and linseed oil) [2,[4][5][6] and also of organic compounds of the same class, like lipidic binders [7][8][9][10], subjected to natural ageing.…”
Section: Introductionmentioning
confidence: 99%
“…These are obvious problems for the analysis of samples of historical interest [4,11,12]. Spectroscopic techniques have the potential to overcome these limitations, as they allow nondestructive and contactless measurements, giving molecular information on complex macromolecules, and could be performed in situ by means of portable devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation